How Neighborhood Poverty Structures Types and Levels of Social Integration. Issue 1 (16th June 2015) - Marcus, Andrea Fleisch; Echeverria, Sandra E.; Holland, Bart K.; Abraido-Lanza, Ana F.; Passannante, Marian R.
Abstract: Social integration is fundamental to health and well‐being. However, few studies have explored how neighborhood contexts pattern types and levels of social integration that individuals experience. We examined how neighborhood poverty structures two dimensions of social integration: integration with neighbors and social integration more generally. Using data from the United States Third National Health and Nutrition Examination Survey, we linked study participants to percent poverty in their neighborhood of residence (N = 16, 040). Social integration was assessed using a modified Social Network Index and neighborhood integration based on yearly visits with neighbors. We fit multivariate logistic regression models that accounted for the complex survey design. Living in high poverty neighborhoods was associated with lower social integration but higher visits with neighbors. Neighborhood poverty distinctly patterns social integration, demonstrating that contexts shape the extent and quality of social relationships.